Evaluating art and design research reflections, evaluation practices and research presentations - Ysebaert, Walter; Kerckhoven, Binke van
Art and design research with its unique nature, its distinct practice-based research process and outcomes differs from scientific research and art and design praxis. The instutionalization of art and design research programmes in the past decade therefore poses major challenges for the parties involved.0The contributions to this book address these challenges in different respects. The first part of the book is devoted to the institutionalization of art and design research in Flanders, the detrimental effects according to some authors, the opportunities it brings according to others. International contributors present an overview of the ways in which the uniqueness, the distinct research process, the exhibition of art and design research outcomes is dealt with in research evaluation practices in Australia, Norway, Sweden and Flanders. The second part of the book showcases investigave paths and subsequent findings followed and found by researchers affiliated to the Flemish Schools of Arts.00The contributions address an audience of art and design research directors, coordinators and researchers and research professionals outside the field. It equally provides artists and designers with a selective overview of research activities being conducted within their domains of interest